Simulasi Pemahaman Robot Pengikut Garis Program C dengan Webots: Simulation Understanding Line Follower Robot C Program with Webots - Alia, Lisana Sidka (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2022)
The line follower robot is one type of robot that develops in the world of technology with a robot system that can follow a line composed of a series of electronic components to get the ideal response and speed. The line follower robot is equipped with sensors that will affect the wheel that is driven by a motor, where the speed is very dependent on the speed limit and friction between the tire robot with the floor. Line follower robot consists of software and hardware systems. In understanding how the line follower robot works use the Webots simulation application as an open source application that can be used by beginners. The line follower robot simulation begins by using the e-puck robot file that has been listed in Webots by inputting the language program used, namely C language, into the robot microcontroller.From the simulation result of line follower robot using Webots were obtained system is capable of identifying a straight line and turn lanes. The system is able to provide an ideal response and speed with input from the line reading sensor which is processed with the C language control system and outputs the result as the robot move maximum.